Analysis of the clinicopathological and imaging features in breast intraductal papillary lesions with or without pathological nipple discharge - Qian Pu; Peng Li; Minghui Su; Dezong Gao (Scientific Reports)
Abstract With the popularity of breast screening, more and more intraductal papillary lesions (IDPL)were detected by ultrasound or mammography, which is a spectrum of diseases ranging from benign to malignant lesions. Patients with pathological nipple discharge (PND) may indicate IDPL, but it is difficult to clarify their biological characteristics before the operation. As to patients with IDPL without PND, it is even an enormous challenge to differentiate their benign or malignant characteristics. Therefore, to avoid inadequate treatment, it is necessary to analyze the clinicopathological and imaging characteristics of patients with papillary lesions before surgery for the preliminary diagnosis of benign or malignant papillary lesions. 267 cases of IDPL with or without PND, namely PND group and non-PND group, were studied using continuous clinical data from October 2020 to September 2023. We analyzed the clinicopathological and imaging characteristics in the two groups of patients with malignancy compared with benign patients. Meanwhile, these characteristics were analyzed in malignant papillary patients with PND or not. 267 patients were pathologically diagnosed with IDPL during three years, accounting for 15.4% of surgical cases of the same period. There were 55 patients with malignant lesions (20.6%), including 28 cases in the PND group (16.5%) and 27 cases in the non-PND group (27.8%), and the incidence of malignant lesions was higher in the non-PND group than that of the PND group. There was a close correlation between age and malignant lesions in the two groups; the number of patients older than 50 years in malignant patients (74.5%) exceeded that of benign patients (42.5%). There were nearly one-third of malignancies in patients with nipple bloody discharge, and the rate increased to 50% when the patient was older than 50 years, but the malignant rate was meager in patients without bloody discharge. There were some factors relating to malignancy in non-PND patients, including age, lesion size, the distance from the nipple to the lesson (DFNL), and abnormal mammogram; there was a significant difference in this positive manifestation between benign and malignant patients. In malignant intraductal papillary lesions, 40.8% of the cases were invasive carcinoma in the non-PND group, higher than in the PND group (10.7%). Meanwhile, immunohistochemistry was more likely to be hormone receptor-positive (92.6%) and Her-2 negative in the non-PND group, compared with the PND group. Breast IDPL is a common disease, among which malignant lesions are higher than reports in previous literature. There are some clinical and imaging manifestations indicating malignancy; patients more than 50 years old with bloody nipple discharge are at high risk of malignancy. When old non-PND patients have more significant lesions, remote DFNL, and abnormal mammograms, there is a high probability of malignancy in them. Although there are different biological characteristics in malignant IDPL with or without PND, they are all low-grade malignancies compared with traditional breast cancer.